ANALISA PERHITUNGAN NILAI JATUH TEGANGAN PADA JARINGAN TEGANGAN MENENGAH SISTEM DISTRIBUSI PT.PLN (PERSERO) RAYON KOTA PONTIANAK - ., Rachmad Nur Herdiansyah (Jurnal Teknik Elektro Universitas Tanjungpura, 2019)
A good electric power system must have good voltage quality and small of power losses. The quality of the voltage and power losses that occur in the medium voltage line can be known by the analysis of voltage drops and active power losses. In this study was analyzed of the medium voltage line distribution system  PLN (Persero) Rayon City of Pontianak used AAAC-S 150 mm2 conductive cable. The analysis carried out of Raya  feeder 7  with a channel length  is 39.95 km and a Raya feeder 10 with a channel length is 27.90 km. Based on the results of calculations, the maximum voltage drop percentage in Raya feeder 7 is 4.52% and Raya feeder 10 is 4.63%. While the maximum current at feeder Raya 7 is 293,254 Ampere with the total active power losses of 66.6204 kW and the maximum current at feeder Raya 10 is 237.418 Ampere with a total active power losses of 55.88462 kW. Based on  the provisions of SPLN No. 72 of 1987 and SNI 04-0225-2000 (PUIL 2000) Feeder Raya 7 and Feeder Raya 10 are still worthy to serve burden and allow for future burden additions.